Phytoplankton of the Paraná River Basin - Devercelli, Melina (2014)
We summarize the information on the phytoplankton of the Paraná River in the Argentine stretch, comparing the density, biomass, functional groups and diversity studies of the mainstem and floodplain since the 70’s. We described the Yacyretá Reservoir and its impact downriver since it started operating in 1994. The spatio-temporal changes of the phytoplankton are associated to the hydrosedimentological regime. Regular variations in the hydrological phases and shorter permanent fluctuations are essential for phytoplankton maintenance, since they allow the lateral exchange with zones of higher algal accumulation in the main channel and with the floodplain. During ordinary hydrological cycles, the mainstem shows a typical potamoplankton, dominated by Aulacoseira granulata and, alternatively, with sub-dominance of Chlorococcales, Cryptophyceae at the Middle and Lower Stretch, Cyanobacteria abound at Yacyretá Reservoir and downriver at the High and the beginning of the Middle Stretch. The disruption of Yacyretá Reservoir produces profound changes in the High Paraná phytoplankton evidenced in increased density and replacement of dominant species; Cryptophyceae replaced the Bacillariophyceae. Since 2001, water transparency increased and phosphorus concentration decreased, as well as the density and diversity of phytoplankton. Since 2004, an increase in Cyanobacteria was observed with bloom of Microcystis aeruginosa that extended 220 km downstream of the dam. Anomalous hydrological cycles, related to the ENSO phenomenon produced changes in phytoplankton density and structure. During El Niño, the system maintains a relative homogeneous phytoplankton assemblage, although mean density values are significantly lower than those registered in ordinary hydrological periods. La Niña provokes a more drastic change in the community, due to the disruption in the exchange with the alluvial valley. The river-floodplain connectivity is essential for the maintenance of phytoplankton diversity.